Príusnice--znovu se vracející infekce? Soucasná situace ve výskytu príusnic ve východoceském regionu - Stĕpánová, V; Plísková, L; Kosina, P; Splino, M; Förstl, M; Bolehovská, R; Dlhý, J; Chrzová, M (Epidemiologie, mikrobiologie, imunologie, 2006)
A review of mumps outbreaks among both non-vaccinated and vaccinated children and young adults in the East Bohemian region in 2003-2005 is presented. A significant increase in mumps cases was observed over this period. The clinical diagnosis was confirmed serologically by ELISA detection of IgM antibodies and/or IgG seroconversion and increased levels of IgG antibodies. A reverse transcriptase nested PCR was introduced for direct detection of mumps virus RNA from clinical specimens (nasopharyngeal secretion, saliva, CSF and serum). The isolated RNA will be stored for further analysis and mumps virus genotyping attempts, helpful in tracing the virus circulation in the East Bohemia region. Possible causes of the recent significant increase in mumps cases among the vaccinated population in the Czech Republic are discussed.
Keywords: dospělí; Female; Infant; dítě; předškolní dítě; Adult; ženské pohlaví; Adolescent; lidé; Aged, 80 and over; Incidence; příušnice; Male; incidence; kojenec; Aged; Czech Republic; Child, Preschool; Česká republika; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Mumps; Middle Aged; mladiství; Humans